Successful recovery from coronavirus disease 2019 in a living kidney transplant recipient using low‐dose methylprednisolone. Issue 1 (5th October 2020) - Tanaka, Ryo; Kakuta, Yoichi; Tsutahara, Koichi; Nakagawa, Masahiro; Ichimaru, Naotsugu; Sakaguchi, Katsuhiko; Kato, Taigo; Imamura, Ryoichi; Nonomura, Norio; Takao, Tetsuya
Abstract : Introduction: The data of immunosuppressive therapy management on solid organ transplant recipients with coronavirus disease 2019 are insufficient. We report a kidney transplant recipient who developed coronavirus disease 2019 pneumonia, with successful management of low‐dose mPSL. Case presentation: A 36‐year‐old man, who underwent living kidney transplantation 1.5 year prior, developed fever. After 10 days, he developed dyspnea, and his blood oxygen levels decreased. Computed tomography showed pulmonary ground‐glass shadow on both lungs, and the coronavirus disease 2019 real‐time polymerase chain reaction test was positive. After reducing the immunosuppressive agents, the C‐reactive protein levels continued elevating, and the pulmonary shadow spread. Subsequently, low‐dose methylprednisolone (40 mg/day) was administered for 4 days and his C‐reactive protein and blood oxygen levels increased and improved, respectively. The coronavirus disease 2019 real‐time polymerase chain reaction test was negative and the pulmonary shadow disappeared. Conclusion: Low‐dose methylprednisolone may prevent the development of severe coronavirus disease 2019.